Implikasi Undang-Undang Nomor 7 Tahun 2021 tentang Pertambahan Tarif PPN 11% terhadap Pelaku Usaha Kerajinan Lokal di Kota Malang - Marsela Rosiana Putri (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2022)
The purpose of this study is to determine the basic considerations for applying the 11% VAT increase and the knowledge of local craft entrepreneurs in Malang City regarding the implications of the 11% VAT. This type of research is normative-empirical juridical, which examines the basis of laws and regulations as research objects and their application in social society. Used a legal and social juridical approach to the community in examining the object of study. Using data sources Law no. 7 of 2021 concerning the Harmonization of Tax Regulations as a scalpel for the application of an 11% VAT increase, as well as the knowledge of local craftsmen in Malang City as objects for an 11% VAT increase. Implementation of Article 7 paragraph (1) Chapter IV concerning Value Added Tax that the value-added tax rate of eleven percent (11%) is enforced from April 1, 2022, the imposition of VAT on taxable goods for transactions carried out by local handicraft entrepreneurs in the form of all goods in the form of handicrafts, unless exemptions are regulated by certain regulations. By Following Article 4 paragraph (1) letter a Value Added Tax is imposed on the delivery of Taxable Goods in the Customs Area by entrepreneurs, while objects of taxable goods according to Law no. 42 of 2009, namely all goods regulated in the VAT Law except for goods: a) taken directly from mining or drilling results, b) basic needs of the community, c) goods in the form of food and drinks that are traded at places to eat as well as by catering services, d) goods in the form of securities, gold bars and also money. So local handicraft products are included in taxable objects that experience VAT rate developments. However, in reality, the community, especially local handicraft entrepreneurs, is only aware of the information on the 11% VAT rate increase and does not apply it to buyers who should be charged VAT.